STUDY OF STABILITY AND THERMAL CONDUCTIVITY OF MULTIWALL CARBON NANOTUBES AND COPPER OXIDE IN ETHYLENE GLYCOL AT MEDIUM TEMPERATURE - MUSTAFA KAMAL, MOHD AIDIL FIRDAUS (IRC, 2020)
The main aim of this study is to prepare a stable MWCNTs / CuO in nanofluid hybrid Ethylene glycol. The experiment will be performed in different amounts and combinations of solid concentrations ranging from 0.01 to 1 per cent each. To prepare the hybrid-nanofluid, the most common method in the preparation of nanofluid which is a 2-step process will be used. Temperatures varying from 20ᵒC to 60ᵒC There will be a few characterization tests to verify the characteristics of the prepared nanofluid. The research that was performed for characterization was the study of particle distribution and thermal conductivity. Graphs shown were the findings at different temperatures of the stability and thermal conductivity of various concentrations of nanoparticles.